2006
DOI: 10.1021/jf052900a
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Preparation of Kaempferol from Green Tea Seed and Its Antioxidant Activity

Abstract: Among the flavonols in green tea, kaempferol has many biological activities but kaempferol of plant origin is too expensive to be used in commercial products. Recently, we confirmed that green tea seed (GTS) contained a reasonable amount of kaempferol glycoside. After conducting structure analysis, two kaempferol glycosides were identified, kaempferol-3-O-[2-O-beta-D-galactopyranosyl-6-O-alpha-L-rhamnopyranosyl]-beta-D-glucopyranoside (compound 1) and kaempferol-3-O-[2-O-beta-D-xylopyranosyl-6-O-alpha-L-rhamno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 13 publications
6
91
0
1
Order By: Relevance
“…Kaempferol 3-O-xylosyl-rutinoside was identified in methanolic extracts of seven onion varieties (Lee, Zweigenbaum, Mitchell, 2013). It has an antioxidant as well as hypoglycemic effect (De Sousa et al, 2004;Park et al, 2006;Torel, Cillard, Cillard, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Kaempferol 3-O-xylosyl-rutinoside was identified in methanolic extracts of seven onion varieties (Lee, Zweigenbaum, Mitchell, 2013). It has an antioxidant as well as hypoglycemic effect (De Sousa et al, 2004;Park et al, 2006;Torel, Cillard, Cillard, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…TNF-α induces the activation of several transcriptional factors, including NF-κB, through TNF-α receptor (TNFR)-dependent signaling pathways (9-11, 15, 16). Flavonoids are widely used to inhibit the activation of NF-κB (17,18), and several studies have shown that flavonoids inhibit the expression of proinflammatory genes in response to inflammatory mediators such as TNF-α (6,19). However, the potential involvement of flavonoids in the regulation of TNF-α -induced IL-8 gene expression in HEK 293 cells has not yet been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…It is converted from hesperidin, with low solubility, to hesperetin 7-O-β-glucoside, which is easy to dissolve in water compared to hesperidin (Sanchez et al, 1987 Mandalari et al, 2006;. Naringinase and hesperidinase have been reported for preparation of aglycones from flavonoid glycosides such as isoliquirtin and kaempferol glycoside (Sato, et al, 2007;Park et al, 2006). Enzymes having pervasive substrate specificity have been reported for preparation of aglycones from flavonoid glycosides.…”
Section: Resultsmentioning
confidence: 99%